(untitled) (Conference Zone, 2022)
This article deals with the prevention of personal aggression or measures to prevent and manifest aggression in the person, changes in the norms of attitude to the manifestation of aggression, verbal forms of aggressive behavior, the development of deceptive and aggressive behavior described in detail.